Lymph Drainage from the Ovine Tonsils: An Anatomical Study of the Tonsillar Lymph Vessels. (5th March 2014) - Casteleyn, C.; Cornillie, P.; Van Ginneken, C.; Simoens, P.; Van Cruchten, S.; Vandevelde, K.; Van den Broeck, W.
Summary Although the tonsils of sheep have gained much attention during the last decade, only few data are available on their lymph vessel architecture. Tonsillar lymph vessels are immunologically important as they form the efferent routes for locally activated immune cells to reach the draining lymph nodes. To gain insight into the tonsillar lymph drainage in the sheep, Indian ink and a casting polymer were injected into the interstitium of the five tonsils present in the heads of slaughtered sheep. This enabled us to determine the draining lymph node and to examine the microscopic organization of lymph vessels using light and scanning electron microscopy. No lymph vessels were observed within the tonsillar lymphoid follicles. The corrosion casts demonstrated that the lymphoid follicles are surrounded by numerous sacculated lymph sinuses that drain into a dense interfollicular lymph vessel network. From here, the lymph flows into single small lymph vessels that in turn drain into larger lymph vessels extending towards the medial retropharyngeal lymph node. The presented results can be valuable for immunological studies, for example during oral or intranasal vaccine development.